Potensi Dan Pengembangan Usaha Tani Jagung Lokal (Zea Mays L.) Petani Desa Ellak Laok Kecamatan Lenteng Kabupaten Sumenep - Silvi Eka Wulandari; Isdiana Suprapti (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
Local corn is corn that has a more savory taste, contains more content with a smaller size, is resistant to pest attacks and takes longer to store. However, the local maize production level of the Lenteng variety is still relatifly low and has not been certified. This study aims to analyze the internal and external factors that affect the level of production of local corn farming, formulate alternative strategies and strategic priorities in the development of local corn farming. Data was collected through interviews with 3 local maize experts and 10 farmer group leaders. Data analysis was performed using IFAS, EFAS, SWOT and QSPM. Based on the results of the SWOT analysis diagram using the IFAS matrix, EFAS is in quadrant I which indicates that the situation is very profitable. Through SWOT and QSPM analysis, three priority strategies were obtained for the development of local corn farming in Ellak Laok Village, namely: (1) improving the performance of farmer groups through savings and loan services for farmer capital, application of biosaka fertilizer from agricultural extension workers. (2) maximizing post-harvest product processing by making processed chips and marning products from local corn. (3) improving the quality of human resources to achieve the maximum amount of local corn production through proper farming system training so that it can meet local demand for corn.